2010
DOI: 10.1002/qj.683
|View full text |Cite
|
Sign up to set email alerts
|

Southern Hemisphere atmospheric circulation response to the El Chichón and Pinatubo eruptions in coupled climate models

Abstract: We study the response of the Southern Hemisphere circulation to the 1982 eruption of El Chichón and 1991 eruption of Pinatubo volcanoes in a suite of up-to-date coupled climate models. We find a significant response in austral spring and autumn in the years following the eruptions, which consists of a stronger stratospheric polar vortex and lowered sea-level pressure over the Antarctic, both consistent with the positive phase of the Southern Annular Mode. The seasonality of the response may be explained in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 31 publications
7
40
0
Order By: Relevance
“…9b,c). These results suggest that although the forced circulation response to Pinatubo appears to be a positive annular mode pattern [as simulated by the CMIP5 models and consistent with the CMIP3 model results of Karpechko et al (2010)], this forced response may be difficult to detect in the observations in the presence of climate variability.…”
Section: Discussion Of Climate Variabilitysupporting
confidence: 57%
See 3 more Smart Citations
“…9b,c). These results suggest that although the forced circulation response to Pinatubo appears to be a positive annular mode pattern [as simulated by the CMIP5 models and consistent with the CMIP3 model results of Karpechko et al (2010)], this forced response may be difficult to detect in the observations in the presence of climate variability.…”
Section: Discussion Of Climate Variabilitysupporting
confidence: 57%
“…9a). While the observed negative SAM has led some studies to suggest that volcanic eruptions may force the circulation into a negative SAM state (e.g., Roscoe and Haigh 2007), other studies have suggested that the El Niño state during and immediately following the eruption may have hidden the forced positive SAM response (e.g., Karpechko et al 2010). The circulation response to El Niño is a negative SAM-like pattern (e.g., L'Heureux and Thompson 2006), and thus, this may have partially or entirely canceled the positive SAM response to the Pinatubo eruption.…”
Section: Discussion Of Climate Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Comparatively little attention has been given to the Southern Hemisphere, or to South America specifically (although see Joseph andZeng, 2011, andWilmes et al, 2012). Some previous work has focused on the Southern Annular Mode in the ERA-40 and NCEP/NCAR reanalysis, in addition to a previous version of NASA Goddard Institute for Space Studies (GISS) Model-E (Robock et al, 2007) and in a subset of CMIP3 models (Karpechko et al, 2010) or in CMIP5 (Gillett and Fyfe, 2013).…”
Section: Volcanic Forcing On Climatementioning
confidence: 99%